A critical analysis of the teaching and learning of number concept in a Grade 2 class in the Western Cape - Scholtz, Marie-Louise (Cape Peninsula University of Technology, 2012)
This action research case study focussed on the teaching and learning of number concept development. The research was conducted in an English Grade 2 class in a primary school in a lower socio-economic community in Manenberg on the Cape Flats, The research is based on the constructivist theories of Piaget, Vygotsky and Feuerstein and was conducted in the paradigm of praxis. The focus of the research was six learners in a class of 43 who were identified by the class educator through the process of continued assessment as needing intervention. Initial data collection was conducted utilising a questionnaire. This instrument was chosen to allow for a gentle introduction and a less threatening means of collecting information from a fellow colleague. I entered the classroom initially as observer and later as participant-observer. I observed how the class teacher taught the superordinate and subordinate concepts of number concept. Some observation sessions were video-recorded to allow for richer data collection. Followup interviews with the class teacher to discuss observations made as well as introduce new teaching methods were audio-recorded. Data were analysed using the process of discourse analysis. I found that the teacher used a variety of different teaching methods, but tended to gravitate to rote teaching with transcription and drill work to develop and consolidate number concept. The learners acquired number concept by implementing previously taught methods without any real understanding. During intervention, it was noted that the focus group fared better when allowed to use concrete equipment.
Thesis (MTech (Education))--Cape Peninsula University of Technology, 2012